A metatheory of the democratic process - Dieter Fuchs (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1993)
The metatheory on the democratic process poses a conceptual framework for the empirical analysis of democratic processes in liberal democracies. A model of democratic processes is being developed which proceeds from certain metatheoretical presuppositions. It distinguishes, inter alia, between three subsystems of the political system and defines their relevant collective actors. Moreover, a concept of political structures and political performance is being proposed to provide theoretically for an empirical explanation of diverse process phenomena by different structural arrangements in liberal democracies. – – Die Metatheorie des demokratischen Prozesses ist ein begrifflicher Bezugsrahmen zur empirischen Analyse der demokratischen Prozesse in den liberalen Demokratien. Ausgehend von bestimmten metatheoretischen Grundannahmen wird ein Modell des demokratischen Prozesses entwickelt. Dieses enthalt u.a. eine Abgrenzung von drei Subsystemen des politischen Systems und eine Bestimmung der relevanten kollektiven Akteure dieser drei Subsysteme. Zur theoretischen Vorbereitung der empirischen Erklarung unterschiedlicher Prozefiphanomene durch unterschiedliche strukturelle Arrangements liberaler Demokratien wird zudem ein Konzept politischer Strukturen und politischer Performanz vorgeschlagen.
Keywords: 300